Nanomechanics of Graphene and Design of Graphene Composites - Liu, Xiaoyi (Springer Theses, Recognizing Outstanding Ph.D. Research, 2019)
This book addresses several important issues concerning the nanomechanics of graphene, an area that is vital to a fundamental understanding of graphene deformation, and to the design of graphene-related materials. The content chiefly focuses on the out-of-plane mechanical behaviors of graphene, and their effects on the mechanical properties of graphene composites. In addition, the book puts forward original theoretical mechanical models based on continuum mechanics, discontinuous effects and atomistic simulations. The findings presented here can provide the basis for valuable guidelines on the design and application of graphene and graphene composites in the field of nanomechanics. .